ChatGPT in Teaching and Learning at University Classes: Are Traditional Pedagogues better Fit? (Interdisciplinary Research in Education, 2025)
This research assesses the connection between collaborating with ChatGPT, note recitation and academic performance in the context of the Master's degree program at Tribhuvan University in Nepal. As teaching and learning paradigms have rapidly changed, students have been confronted with the need to blend traditional lecturing pedagogical methods with the inevitable inclusion of AI technologies. This study utilized a mixed method (QUAN-qual) approach with quantitative data from sample sizes of 280 university students and interview data from 10 university students. The results indicated that collaborating with ChatGPT significantly affected students performance, (path coefficient, 0.32 (t=3.01, p